Exnovation of Low Value Care: A Decade of Prostate‐Specific Antigen Screening Practices. Issue 1 (6th October 2018) - Bynum, Julie; Passow, Honor; Carmichael, Donald; Skinner, Jonathan
Abstract : Objectives: To examine prostate‐specific antigen (PSA) screening practice change in subgroups of men defined in guidelines and in various regions and to identify factors associated with change in screening practices. Design: Observational study using serial cross‐sections, 2003 to 2013. Setting: National fee‐for‐service Medicare. Participants: Men aged 68 and older eligible for prostate cancer screening. Measurements: National PSA screening practices in men aged 68 and older from 2003 to 2013 and change in regional screening rates in men aged 75 and older. Results: The PSA screening rate in men aged 68 and older was 17.2% in 2003, 22.3% in 2008, and 18.6% in 2013 (p < .001 for all differences); rates ended slightly lower than rates in 2003 only in men 80 and older. Racial disparities in screening became less pronounced over this period. In men aged 75 and older, change in regional screening rates varied widely, with absolute rates growing by 15 per 100 enrollees in some areas and declining by the same amount in others. Areas with high social capital, a measure associated with diffusion of new ideas, were more likely to decline; malpractice intensity and managed care penetration had no effect. Conclusion: Studying Medicare enrollees over time, we found little reduction in PSA screening and even increases according to race and in some regions. The heterogeneous changes across regions suggest that consistent reduction in the use of low‐value care may require change strategies that go beyond evidence and guidelines to include monitoring and feedback on performance.J Am Geriatr Soc 67:29–36, 2019.